PEGylated Elesclomol@Cu(Ⅱ)-based Metal‒organic framework with effective nanozyme performance and cuproptosis induction efficacy for enhanced PD-L1-based immunotherapy - Xufeng Lu; Wenhai Deng; Shuaibin Wang; Shengsheng Zhao; Bingzi Zhu; Binglong Bai; Yiwen Mao; Ji Lin; Yongdong Yi; Zuoliang Xie; Xiang Wang; Yongyong Lu; et al. (Materials Today Bio)
Nanozymes constitute a promising treatment strategy for antitumor therapy. However, the catalytic function of metal‒organic framework (MOF)-based nanozymes during cuproptosis remains unclear. In this study, a Cu(Ⅱ)-based MOF nanocomposite loaded with the copper ionophore elesclomol and surface modified with polyethylene glycol polymer (PEG) was developed (ES@Cu(Ⅱ)-MOF) for effective cuproptosis induction. The peroxidase (POD)-like activity of ES@Cu(Ⅱ)-MOF generated an abundance of hydroxyl radicals (•OH) via a Fenton-like reaction, and its glutathione peroxidase (GSH-Px)-like activity converted Cu2+ into more toxic Cu+ ions to efficiently consume endogenous GSH. Notably, the rapid accumulation of Cu+ and ES in tumor cells induced the aggregation of lipoylated dihydrolipoamide S-acetyltransferase (DLAT) and the downregulation of Fe‒S cluster proteins, ultimately leading to cuproptosis. ES@Cu(Ⅱ)-MOF exhibited extraordinary cytotoxicity against breast cancer cells in vitro and significantly suppressed 4T1 breast tumor growth in vivo. Moreover, ES@Cu(Ⅱ)-MOF induced immunogenic cell death (ICD) to increase the antitumor immune response. Furthermore, combining ES@Cu(Ⅱ)-MOF with an anti-programmed cell death-ligand 1 (PD-L1) antibody converted the immunosuppressive tumor microenvironment to an immunogenic microenvironment, thus effectively inhibiting breast tumor growth. Overall, this work provides an innovative approach utilizing nanozymes to facilitate cuproptosis for cancer treatment, which potentially enhances the effectiveness of immune checkpoint inhibitor-based immunotherapy.